Oxidative stress-dependent frataxin inhibition mediated alcoholic hepatocytotoxicity through ferroptosis. (1st December 2020) - Liu, Jingjing; He, Hui; Wang, Jing; Guo, Xiaoping; Lin, Hongkun; Chen, Huimin; Jiang, Chunjie; Chen, Li; Yao, Ping; Tang, Yuhan
Graphical abstract: Highlights: Ethanol inhibited frataxin expression and oxidative stress was partly involved in. Ethanol induced ferroptosis signature phenotypes in mouse livers. Proteomic analysis suggested frataxin deficiency was associated with ferroptosis. Frataxin deficiency exacerbated the sensitivity to ethanol-induced ferroptosis. Restoring frataxin alleviated ethanol-mediated ferroptosis. Abstract: Alcoholic liver disease (ALD) is one of the severe liver diseases, resulting in high morbidity and mortality. However, frataxin, a mitochondrial protein mainly participating in iron homeostasis and oxidative stress, remains uncertain in the pathogenesis of ALD. In the present study, the role of frataxin in ALD was investigated. Ethanol (100 mM) decreased frataxin expression at 48 and 72 h in HepG2. Dramatically, in HepG2 overexpressing cytochrome P450 2E1 (HepG2 CYP2E1+/+ ), frataxin level was down-regulated with ethanol stimulation at 12 h. Moreover, chronically feeding ethanol to mice via Lieber-DeCarli liquid diet (30 % of total calories) for 15 weeks significantly inhibited frataxin expression. Ferroptosis signature proteins were dysregulated, accompanied by mitochondrial damage of morphology, enhanced malondialdehyde and decreased glutathione in the liver, as well as accumulation of reactive oxygen species and mitochondrial labile iron pool in primary hepatocytes. Notably, proteomics screening of frataxin deficient-HepG2 further suggested frataxin was associated with ferroptosis. Furthermore, the ferroptosis inhibitor ferrostatin-1 blocked the increase of lactate dehydrogenase release by ethanol in HepG2 CYP2E1+/+ . Most importantly, frataxin deficiency enhanced ferroptosis driven by ethanol via evaluating the levels of lactate dehydrogenase, cell morphological changes, mitochondrial labile iron pool, and lipid peroxidation. Conversely, restoring frataxin alleviated the sensitivity to ferroptosis. In addition, frataxin overexpression mitigated the sensitivity of ethanol-induced ferroptosis in HepG2 CYP2E1+/+ . Collectively, our study revealed that frataxin-mediated ferroptosis contributed to ALD, highlighting a potential therapeutic strategy for ALD.